Rancang Bangun Unit Destilasi Solar Heater - Asep Ruchiyat (Politeknosains, 2018)
The difficulty of the community in the coastal areas in meeting the needs of clean water until now a problem that has not been solved. An alternative effort that can be done for the provision of clean water is to utilize seawater through several processing processes. One of the practical processing and environmentally friendly way is through the process of solar energy distillation. Distillation is another term for distillation, ie the heating process of a material at various temperatures, without contact with the outside air. The purpose of this research is to know the working system of distillation of solar energy of type two roof, with working principle of destilator tool placed in place not protected by sunlight, container of destilator filled with seawater as much as 40 liters with height 10 cm from destilator container surface. Based on the analysis of research that has been done, the temperature of the environment and the temperature of the glass is not much different and the changes are directly proportional because the absorption of heat on the glass is very small. For hot water temperatures compared to ambient temperatures and glass temperatures, the temperature changes are not too fast due to the influence of water-absorbing power and the absorption of hot sand which becomes the base of the distillator, so that the water temperature is higher than the ambient temperature and the glass temperature. The faster the temperature of the environment and the temperature of the glass goes down the more clean water is produced.